Developments in industrial action 2005 - 2009 - Carley, Mark (Dublin, 2010)
"This overview examines developments in industrial action across the European Union and Norway over 2005–2009. The most ‘strike-prone’ countries during the period were Denmark, France and Belgium, while Austria, Estonia and Latvia were essentially strike-free, and the level of industrial action in the new Member States was only about a quarter of that in the EU15. Manufacturing was the sector most prone to conflict, followed by the broad public sector and transport and communications. Pay disputes were the most common cause of industrial action."